Brief Report: The Impact of Disease Stage on Early Gaps in ART in the "Treatment for All" Era—A Multisite Cohort Study. (15th April 2021) - Katz, Ingrid T.; Musinguzi, Nicholas; Bell, Kathleen; Cross, Anna; Bwana, Mwebesa B.; Amanyire, Gideon; Asiimwe, Stephen; Orrell, Catherine; Bangsberg, David R.; Haberer, Jessica E.
Abstract : Background: Adoption of "Treat All" policies has increased antiretroviral therapy (ART) initiation in sub-Saharan Africa; however, unexplained early losses continue to occur. More information is needed to understand why treatment discontinuation continues at this vulnerable stage in care. Methods: The Monitoring Early Treatment Adherence Study involved a prospective observational cohort of individuals initiating ART at early-stage versus late-stage disease in South Africa and Uganda. Surveys and HIV-1 RNA levels were performed at baseline, 6, and 12 months, with adherence monitored electronically. This analysis included nonpregnant participants in the first 6 months of follow-up; demographic and clinical factors were compared across groups with χ 2, univariable, and multivariable models. Results: Of 669 eligible participants, 91 (14%) showed early gaps of ≥30 days in ART use (22% in South Africa and 6% in Uganda) with the median time to gap of 77 days (interquartile range: 43–101) and 87 days (74, 105), respectively. Although 71 (78%) ultimately resumed care, having an early gap was still significantly associated with detectable viremia at 6 months ( P ⩽ 0.01). Multivariable modeling, restricted to South Africa, found secondary education and higher physical health score protected against early gaps [adjusted odds ratio (aOR) 0.4, 95% confidence interval (CI): 0.2 to 0.8 and (aOR 0.93, 95% CI: 0.9 to 1.0), respectively]. Participants reporting clinics as "too far" had double the odds of early gaps (aOR 2.2: 95% CI: 1.2 to 4.1). Discussion: Early gaps in ART persist, resulting in higher odds of detectable viremia, particularly in South Africa. Interventions targeting health management and access to care are critical to reducing early gaps.